2023
DOI: 10.3389/fmicb.2023.1227297
|View full text |Cite
|
Sign up to set email alerts
|

Conservation tillage practices affect soil microbial diversity and composition in experimental fields

Abstract: IntroductionConservation tillage is a widely used technique worldwide, but the effects of conservation tillage on bacterial community structure are poorly understood. We explored proportional alterations in the bacterial community under different tillage treatments.MethodologyHence, this study utilized high-throughput sequencing technique to investigate the structure and assembly processes of microbial communities in different tillage treatments.Results and discussionTillage treatments included tillage no-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Although NT initially has a positive effect on soil RES, a mulch layer on the soil surface could be a hindrance. Khan et al [47] have reported similar findings by observing a decline in soil RES over time under CT practices with NT and straw retention, reporting that a thick mulch layer could act as a physical barrier, reducing oxygen availability in NT fields and providing a slow release of carbon.…”
Section: Soil Microbial Respirationmentioning
confidence: 58%
“…Although NT initially has a positive effect on soil RES, a mulch layer on the soil surface could be a hindrance. Khan et al [47] have reported similar findings by observing a decline in soil RES over time under CT practices with NT and straw retention, reporting that a thick mulch layer could act as a physical barrier, reducing oxygen availability in NT fields and providing a slow release of carbon.…”
Section: Soil Microbial Respirationmentioning
confidence: 58%
“…Conservation tillage practices affect the soil composition and microbial diversity [79]. The reduced mechanical intervention in the soil, mulching, increased carbon sequestration, smaller changes in the amount and temperatures of water and air that typify conservation soil cultivation create favourable conditions for microorganisms [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Soil tillage significantly influences the physical, chemical, and biological properties of the soil (Ding et al, 2020;Gondal et al, 2021;Khan et al, 2023;Douibi et al, 2024). The way it is performed has undergone major changes in recent years.…”
Section: Introductionmentioning
confidence: 99%